Konstruksi Realitas Media Online terhadap Isu Konservasi Gajah Sumatera: Analisis Framing Model Entman Pada Tempo.co dan Kompas.com - Agustina Widyawati (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines how online media shapes social reality related to Sumatran elephant conservation through news framing. Online media plays a strategic role in shaping public understanding of environmental and conservation issues, including conflicts between humans and wildlife involving endangered species. This study aims to analyze the framing of Sumatran elephant conservation issues in Tempo.co and Kompas.com using Robert N. Entman's framing model, which consists of problem definition, causal interpretation, moral evaluation, and recommendations for action. This study uses a qualitative approach with framing analysis as the research method. This review analyzes 5 articles from Tempo.co and 5 articles from Kompas.com in the period July-December 2025. The results show that Tempo.co frames the issue of Sumatran elephant conservation as a structural ecological crisis that focuses on criticism of policies, deforestation, and weaknesses in government and corporate governance. In contrast, Kompas.com uses a socio-institutional approach that emphasizes technical rescue measures, the active role of conservation agencies, and the symbolic value of elephants as a national identity. These differences in framing show that online media actively construct reality rather than merely reflecting events. This study highlights the importance of critical media literacy in understanding environmental discourse in digital journalism.